2018
DOI: 10.1111/1462-2920.14463
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random processes determine the colonization of groundwater sediments by microbial communities in a pristine porous aquifer

Abstract: Summary Sediments accommodate the dominating share of groundwater microbiomes, however the processes that govern the assembly and succession of sediment‐attached microbial communities in groundwater aquifers are not well understood. To elucidate these processes, we followed the microbial colonization of sterile sediments in in situ microcosms that were exposed to groundwater for almost 1 year at two distant but hydrologically connected sites of a pristine, shallow, porous aquifer. Our results revealed intrigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 78 publications
(171 reference statements)
1
14
0
Order By: Relevance
“…Conversely, in this study, we explored which factors drive biofilm assembly on a pre-colonized surface, which is especially relevant when applying bioaugmentation for in-situ bioremediation of natural environments (Tyagi et al, 2011) or wastewater treatment (Herrero and Stuckey, 2015). In groundwater, it has been shown that the composition of sediment-attached communities can differ substantially compared to suspended planktonic communities (Fillinger et al, 2019; Lehman et al, 2001), therefore, using MFC reactors as a model system allows full control of the environmental conditions and easily differentiating between surface-attached (i.e. anodic biofilm) and suspended communities (Zhang et al, 2019; Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in this study, we explored which factors drive biofilm assembly on a pre-colonized surface, which is especially relevant when applying bioaugmentation for in-situ bioremediation of natural environments (Tyagi et al, 2011) or wastewater treatment (Herrero and Stuckey, 2015). In groundwater, it has been shown that the composition of sediment-attached communities can differ substantially compared to suspended planktonic communities (Fillinger et al, 2019; Lehman et al, 2001), therefore, using MFC reactors as a model system allows full control of the environmental conditions and easily differentiating between surface-attached (i.e. anodic biofilm) and suspended communities (Zhang et al, 2019; Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…the time to reach stable maximal current generation) showed different microbial electroactive communities once in steady state. While most studies focus primarily on biofilm formation on clean surfaces (Brislawn et al, 2019; Fillinger et al, 2019; Zhang et al, 2019; Zhou et al, 2013), here we explored the effect of community assembly processes when the anode surface was pre-colonized (bioaugmented) by a defined electroactive consortium (designated as EDC) on MFC startup. Such pre-colonization is expected to enhance deterministic factors relative to stochastic ones in the formation of the mature, anode biofilm at steady state.…”
Section: Introductionmentioning
confidence: 99%
“…Using 16S rRNA amplicon sequencing and shotgun metagenomic approaches, Lau, Zarkasi, Md Sah, and Shu-Chien (2019) investigated microbial communities in the photic and aphotic zones of an aquaculture site and an undisturbed site in a tropical human-made freshwater lake. Fillinger, Zhou, Kellermann, and Griebler (2019) followed the microbial colonization of sterile sediments in microcosms exposed to groundwater in two porous aquifers over a year. Using 16S rRNA amplicon sequencing, the authors showed that sediment surfaces selected for specific groups of microorganisms that assembled over time in a reproducible, non-random way.…”
Section: Bacterial Ecologymentioning
confidence: 99%
“…To our knowledge, no studies have examined the physical location of ETBE-biodegrading activity in an aquifer, that is, the relative contribution of suspended and attached microbial communities to this potential. However, is it known that the taxonomy of attached and suspended microbial communities in aquifers can differ (Alfreider et al 1997;Rizoulis et al 2013;Hug et al 2015;Smith et al 2018;Fillinger et al 2019). Interestingly, several studies have investigated the colonisation of functionally-important GEO-degrading organisms on inert surfaces used in bioreactors (Kharoune 2001;Purswani et al 2011;Hicks et al 2014;Alfonso-Gordillo et al 2016;Guisado et al 2016).…”
Section: Introductionmentioning
confidence: 99%